Teacher self-efficacy and enthusiasm: Relations to changes in student-perceived teaching quality at the beginning of secondary education. (June 2021) - Lazarides, Rebecca; Fauth, Benjamin; Gaspard, Hanna; Göllner, Richard
Abstract: Teaching quality is a key factor in student academic success, but few studies have investigated how teaching quality changes at the beginning of secondary education and how such changes are predicted by dimensions of teacher motivation. This study investigated the changes in class-level student perceptions of teaching quality over one school year at the beginning of secondary school and examined how teachers' self-efficacy and enthusiasm predicted such changes. Data from 1996 students (53.8% male; mean age: 11.09 years, SD = 0.55) and their homeroom teachers ( N = 105), who were surveyed at the beginning of Grades 5 and 6, were analyzed. Results showed a significant decline in class-level student-perceived emotional support, classroom management, and instructional clarity. Teacher-reported self-efficacy was not significantly related to changes in teaching quality. Teacher-reported enthusiasm buffered the decline in students' class-level classroom management. Highlights: We used multilevel latent change modeling with student and teacher data. Class-level classroom management and support declined from Grade 5 to 6. Teacher-reported enthusiasm reduced the decline in class-level classroom management. Teacher-reported self-efficacy did not associate with changes in teaching quality.